Abundance, density and size structure of Mellitella stokesii (Echinolampadacea: Mellitidae) in sandbanks of El Tamarindo estuary, El Salvador - Ramos-Cáceres, María Fernanda (2024)
Introduction: Irregular echinoids are characterized by having a selection of the substrate mainly on soft bottoms. In El Salvador, seven species of irregular echinoids have been recorded on the main sandy beaches of the country, M. stokesii is one of them. Objective: Determine the abundance, density and size structure of M. stokesii on beaches at the mouth of the El Tamarindo estuary, El Salvador. Methods: The research was carried out in the dry season in the east of the country on the beaches of the El Tamarindo estuary, which is characterized by large extensions of sand mixed with organic matter. At each site, band transects parallel to the coast were plotted by  9 quadrants of 10 m2 separated from each other by 10 m (total area of 90 m2), where individuals of M. stokesii found within the delimited area were counted and measured. Results: 958 individuals of M. stokesii were counted with a total density of 10.64 ± 13.22 ind/m2. The size range was 1–6.5 cm.  The habitat was characterized by presenting sand with organic matter in the first mm of the substrate in the company of other invertebrates. Conclusions: The abundance and density of M. stokesii are similar to the ones recorded in other studies in the region.